Soyuz mishap sounds alarms. - Oberg, J. (IEEE spectrum)
An unsettling event during a Soyuz spacecraft's descent from the International Space Station (ISS) on 3 May was an unwelcome reminder of the outpost's complete dependence on the Russian vehicle for trips back and forth to Earth-until the US shuttle fleet is back in action. It also was a reminder that reliable software can be almost as critical as reliable hardware in space, especially when working with unfamiliar equipment. So when contact with the capsule was lost about 15 minutes before landing. For two hours there was no word on the fate of the crew. The problem was a software glitch in the new control computer that had apparently confused the spacecraft's navigation system. Instead of enduring a maximum G-force of 4 to 5 for about a minute as the vehicle decelerated during the planned shallow glide approach to the landing point, the crew suddenly faced twice that amount as the capsule plunged steeply into the atmosphere before reaching the ground 450 km short of where rescue teams were waiting.